FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERKEMBANGAN PSIKOSOSIAL PADA ANAK USIA PRASEKOLAH - Nur Amalina Salsabila; Istiqomah, Nurul; Enikmawati, Anik (JURNAL KEPERAWATAN, 2023)
Background : The psychosocial development of preschool-aged children is related to several factors, including the family environment, educational level of caregiver, and status of caregiver's employment. Because a child's psychosocial development will have an impact on the child's future, it is important for caregivers to pay attention to all factors that may positively impact the psychosocial development of preschool-age children. Objective : to determine the relationship between family environment, caregiver's level of education, and caregiver's employment status with the psychosocial development of preschool-age children at RA Perwanida Pandeyan. Methods : quantitative research and through a cross sectional approach. The research sample was taken using proportionate stratified sampling technique with sample size 60. The instruments used in this research used a psychosocial development questionnaire for preschool children, a Brief Family Relationship Scale questionnaire, and a demographic questionnaire. Results : This research shows that the majority of RA Perwanida's students have initiative psychosocial development (78.33%), the majority are 6 years old, 60% are male, with a dominant family environment (80%), the majority of caregivers have completed high school education (46.67%), and the majority of caregivers did not work (61.67%). Conclusion : there is a relationship between the variables of psychosocial development of preschool-age children with family environment and status of caregiver's employment, while there is no relationship with the educational level of caregiver Keywords: education level; employment status; family environment; psychosocial development; preschool-aged children